-46+11x=-7x-2(-4x+8)

Simple and best practice solution for -46+11x=-7x-2(-4x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -46+11x=-7x-2(-4x+8) equation:



-46+11x=-7x-2(-4x+8)
We move all terms to the left:
-46+11x-(-7x-2(-4x+8))=0
We calculate terms in parentheses: -(-7x-2(-4x+8)), so:
-7x-2(-4x+8)
We multiply parentheses
-7x+8x-16
We add all the numbers together, and all the variables
x-16
Back to the equation:
-(x-16)
We get rid of parentheses
11x-x+16-46=0
We add all the numbers together, and all the variables
10x-30=0
We move all terms containing x to the left, all other terms to the right
10x=30
x=30/10
x=3

See similar equations:

| 5-2x=x=1 | | -4/7z-2=38 | | 160=6-11x | | 8a+6=-2 | | 2+57x=58x | | 1/6c+1/3=-2 | | g÷-7=3 | | F(x)=(2x+7)/(3x-9) | | -6-9k=165 | | -5x2-3x=0 | | 2+21x=50 | | 0.05=1/2^n | | 59=10+7t | | 4u+3-2(-6u-1)=4(u-1) | | -9v-11=-5(v-5) | | 5.6w^2=7w+18 | | 5x+(6−2x)=−(14+2x) | | -7y+5(y+7)=19 | | 11^2x=16 | | 2w+41=91 | | X=y/5+16 | | 6xx=54 | | 22x-5=3(6x-4)+4x+7 | | 15.3+x=22.5 | | F(x)=-x^2-9x+20 | | 8x⁶+215x³-27=0 | | Y=x³+7x-5 | | x-2-x5-x4-23=0 | | 4)4+x)=2(x-8) | | 9=p/3-11 | | 128=x+140 | | 3x−2=46x−4=8 |

Equations solver categories